2022
DOI: 10.1038/s41588-022-01034-x
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in bipolar disorder identifies AKAP11 as a risk gene shared with schizophrenia

Abstract: B. M. (2022). Exome sequencing in bipolar disorder identifies AKAP11 as a risk gene shared with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 56 publications
2
86
0
Order By: Relevance
“…A consistent observation in exome-based analyses of neuropsychiatric disorders is an enrichment of significant associations in constrained genes 6,7 . Indeed, in the top quintile of constrained genes, burden heritability is 15.9x (SE = 1.7x) enriched for schizophrenia and 4.4x (SE = 1.2x) enriched for bipolar disorder (Figure 6B).…”
Section: Burden Heritability Of Schizophrenia and Bipolar Disordermentioning
confidence: 65%
See 1 more Smart Citation
“…A consistent observation in exome-based analyses of neuropsychiatric disorders is an enrichment of significant associations in constrained genes 6,7 . Indeed, in the top quintile of constrained genes, burden heritability is 15.9x (SE = 1.7x) enriched for schizophrenia and 4.4x (SE = 1.2x) enriched for bipolar disorder (Figure 6B).…”
Section: Burden Heritability Of Schizophrenia and Bipolar Disordermentioning
confidence: 65%
“…Burden heritability is also more strongly concentrated in constrained genes (median enrichment: 4.5x vs. 2.1x for common variants), indicating that negative selection affects common- and rare-variant architecture differently. Finally, we find that burden heritability for schizophrenia and bipolar disorder 6,7 is especially high (3.8% and 3.6%). Our results show that there are a tractable number of large-effect genes to discover by studying rare variants, that common and rare associations are mechanistically convergent, and that rare coding variants will contribute only modestly to missing heritability and population risk stratification.…”
mentioning
confidence: 73%
“…Analysis conducted by Andlauer et al [27] on BIP multiplex families have shown that unlike familial SCZ cases studied here, familial BIP cases have a significantly higher BIP PRS compared to ancestry matched, sporadic cases. These results, in addition to sparse evidence for the involvement of rare risk variation in the genetic architecture of BIP [22], demonstrates the importance of common risk variation in familial BIP, whereas whole exome sequencing studies of SCZ in both family and case-control samples have demonstrated that in addition to common variation, rare variation also plays an important role in the genetic architecture of SCZ [21,[51][52][53].…”
Section: Discussionmentioning
confidence: 91%
“…Another explanation is that the increased recurrence risk in multiplex families may be attributable to segregation of rarer, higher risk variation, identifiable through exome or whole-genome sequencing likely in combination with common risk variation. Sequencing studies suggest that rare, deleterious variation in the genome is involved in the genetic etiology of SCZ and other psychiatric disorders [15][16][17][18][19][20][21][22], but the extent to which rare variation contributes to SCZ risk in multiplex families is currently unknown. A third hypothesis, not addressed here, is that familial cases may have increased exposure to environmental risks unique to the families that may explain the higher recurrence risk in multiplex families.…”
Section: Introductionmentioning
confidence: 99%
“…We also downloaded rare segregating variants in cases and controls, available publicly for epilepsy, autism, schizophrenia, and bipolar disorder (10,12,14,17). Note that each study defined rare variants based on their own criteria: for example, the autism study designates rare variants as those with “allele frequency ≤ 0.1% in our dataset and non-psychiatric subsets of reference databases” (14).…”
Section: Methodsmentioning
confidence: 99%